Principles of inorganic materials design - Lalena, John N. (Wiley-Interscience, 2005)
This book discusses a number of topics that are pertinent to the design of new inorganic materials but are typically not covered in standard solid-state chemistry books. The authors start with an introduction to structure at the mesoscopic level and progress to smaller-length scales. Next, detailed consideration is given to both phenomenological and atomistic-level descriptions of transport properties, the metal-nonmetal transition, magnetic and dielectric properties, optical properties, and mechanical properties. Finally, the authors present introductions to phase equilibria, synthesis, and nanomaterials